2022
DOI: 10.1007/s00406-022-01467-9
|View full text |Cite
|
Sign up to set email alerts
|

One-year results from the vaccination campaign against COVID-19 infection in 47 million individuals with severe mental disorders and other chronic diseases

Abstract: Severe mental disorders have been associated with increased COVID-19 mortality. The aim of this study was to evaluate the results of the vaccination campaign against COVID-19 after 1 year using exhaustive population-based data. In this nationwide population-based study, we used data from the French national medico-administrative database (SNDS) and the COVID Vaccine teleservice from January 4, 2021 (date of activation of the teleservice) to January 30th, 2022. As of January 30th, 2022, the rate of first inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…However, the percentage of PWUD who received dose 2 is still on level with the total Norwegian population (19). In contrast, several studies have found a lower cumulative vaccine uptake mong PWUD compared to the general population (51)(52)(53)(54)(55)(56). Some studies suggest that this can be explained by hesitancy towards the vaccines among PWUD (52,54).…”
Section: Discussionmentioning
confidence: 97%
“…However, the percentage of PWUD who received dose 2 is still on level with the total Norwegian population (19). In contrast, several studies have found a lower cumulative vaccine uptake mong PWUD compared to the general population (51)(52)(53)(54)(55)(56). Some studies suggest that this can be explained by hesitancy towards the vaccines among PWUD (52,54).…”
Section: Discussionmentioning
confidence: 97%
“…Harm-reduction measures such as needle sharing programs indeed postulate that their target group is willing and proficient to adopt healthy behaviors (38). Finally, the huge differences in vaccination rates reported for different countries such as the France, USA, Spain, and Mexico [e.g., (19)(20)(21)(22)], may suggest a relevant influence of context factors such as the characteristics of the national/local health system.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding COVID-19, studies focusing on OMTP showed considerable variations regarding vaccine hesitancy during the first year of the pandemic: studies from Australia, USA, and Norway showed 20–40% rates of self-reported vaccination rejection ( 16–18 ), whereas studies from France, Spain, Australia, USA, and Mexico showed hesitancy in >70% ( 19 , 20 ), 49% ( 15 ), 38% ( 21 ), and 38% ( 22 ), respectively. What these studies have in common is that vaccination completion rates in PWID were much lower than the rates that were observed in the surrounding general adult population.…”
Section: Introductionmentioning
confidence: 99%
“…Although the dual vaccination rate achieved in this study of 86.7% was slightly lower than the general population, they are substantially higher than national and international rates. In total, ~50% of Australian NSP attendees have received dual vaccination, 9 while 69.4% of people with Opioid Use Disorder (OUD) in France 25 and 71% of people attending a Spanish OTP clinic had double vaccination. 6 …”
Section: Discussionmentioning
confidence: 99%